Blocking by Histones of Accessibility to DNA in Chromatin: Addition of Histones - Mirsky, Alfred E. (1972)
The blocking effect of histones on accessibility of DNA to DNase has been studied by addition of various histones to chromatin in intact or histone-depleted thymus nuclei (those from which all lysine-rich histone was removed and those from which much of the arginine-rich histone was removed) and to deoxyribonucleoprotein (chromatin) extracted from nuclei. In each case lysine-rich histone, weight for weight, blocks accessibility more effectively than does arginine-rich histone. Fractions of the arginine-rich histone differ considerably from each other in their blocking efficacy. Phosphorylation of lysine-rich histone tempers its blocking effectiveness.